2019
DOI: 10.1098/rsif.2019.0285
|View full text |Cite
|
Sign up to set email alerts
|

Weak radiofrequency fields affect the insect circadian clock

Abstract: It is known that the circadian clock in Drosophila can be sensitive to static magnetic fields (MFs). Man-made radiofrequency (RF) electromagnetic fields have been shown to have effects on animal orientation responses at remarkably weak intensities in the nanotesla range. Here, we tested if weak broadband RF fields also affect the circadian rhythm of the German cockroach ( Blatella germanica ). We observed that static MFs slow down the cockroach clock rhythm under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…This is also evidenced by significant correlations between the studied here behavioral endpoints and experimental magnetic fluctuations. Earlier, it was reported that magnetic influence could affect circadian rhythms in different organisms [41,42]. However, until the present study, there were no direct experimental data in support of the entrainment of endogenous circadian oscillators to slow magnetic fluctuations.…”
Section: Discussioncontrasting
confidence: 54%
“…This is also evidenced by significant correlations between the studied here behavioral endpoints and experimental magnetic fluctuations. Earlier, it was reported that magnetic influence could affect circadian rhythms in different organisms [41,42]. However, until the present study, there were no direct experimental data in support of the entrainment of endogenous circadian oscillators to slow magnetic fluctuations.…”
Section: Discussioncontrasting
confidence: 54%
“…It is also well-known that the superoxide radical, , can be an alternative partner for the flavin radical 58 61 . It has also been proposed that RPs can play important roles in the magnetosensitivity of Drosophila ’s CC 21 , 25 , 62 .…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s, Brown et al [11] found that small changes in the intensity of Earth’s MF synchronize the CCs of fiddler crabs and other organisms. Since then, the effects of external MF on the CC have been observed in multiple studies [12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24]. Similarly, Yoshii et al [25] have shown the effects of static MFs on the CC of Drosophila and found that exposure to these fields exhibited enhanced slowing of clock rhythms in the presence of blue light, with a maximal alteration at 300 µ T, and reduced effects at both lower and slightly higher field strengths.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known that the superoxide radical, O 2 •– , can be an alternative partner for the flavin radical [58, 59, 60, 61]. It has also been proposed that RPs can play important roles in the magnetosensitivity of Drosophila ’s CC [21, 25, 62].…”
Section: Introductionmentioning
confidence: 99%